In harm's way: the dynamics of urban violence - Auyero, Javier (Princeton University Press, 2015)
"Arquitecto Tucci, a neighborhood in Buenos Aires, is a place where crushing poverty and violent crime are everyday realities. Homicides--often involving young people--continue to skyrocket, and in the emergency room there, victims of shootings or knifings are an all-too-common sight. In Harm's Way takes a harrowing look at daily life in Arquitecto Tucci, examining the sources, uses, and forms of interpersonal violence among the urban poor at the very margins of Argentine society.Drawing on more than two years of immersive fieldwork, sociologist Javier Auyero and María Berti, an elementary school teacher in the neighborhood, provide a powerful and disarmingly intimate account of what it is like to live under the constant threat of violence. They argue that being physically aggressive becomes a habitual way of acting in poor and marginalized communities, and that violence is routine and carries across various domains of public and private life. Auyero and Berti trace how different types of violence--be it criminal, drug related, sexual, or domestic--overlap, intersect, and blur together. They show how the state is complicit in the production of harm, and describe the routines and relationships that residents, particularly children, establish to cope with and respond to the constant risk that besieges them and their loved ones.Provocative, eye-opening, and extraordinarily moving, In Harm's Way is destined to become a classic work on violence at the urban margins"--